Dilemmatic of Management of Wound Care of Diabetic for Risk Amputation in Rural Areas: A Case Report - Harsah Bahtiar Zainudin; Tantut Sutanto; Suhari Suhari (Indonesian Journal of Global Health Research, 2025)
Diabetic wounds are one of the most challenging complications faced by individuals with diabetes. These wounds not only pose serious physical threats, such as infection and limb loss, but also cause significant psychological distress. One ethical dilemma commonly encountered in diabetic wound care involves decision-making about treatment options, especially when patients request amputation due to pain or economic burden, while healthcare providers aim to preserve the limb through advanced wound care techniques. This situation requires careful consideration of both medical and ethical aspects to ensure patient-centered care. The objective of wound care in such cases is not only physical healing but also improving the patient’s psychological well-being. When care is holistic and empathetic, patients are more likely to engage in treatment positively and without fear, especially during painful procedures such as dressing changes. This case highlights a 55-year-old man with a 20-year history of uncontrolled diabetes and a chronic, infected wound on his right leg. The patient's initial desire for amputation was addressed through a multidisciplinary approach using the TIME method Tissue management, Inflammation control, Moisture balance, and Epithelial advancement. The structured, ethical, and compassionate care helped the patient reconsider amputation, demonstrating that rural nurses and health teams can resolve ethical dilemmas and support better patient outcomes.